2007
DOI: 10.1186/1747-597x-2-3
|View full text |Cite
|
Sign up to set email alerts
|

Negative consequences associated with dependence in daily cannabis users

Abstract: Background: Cannabis is the most widely consumed illicit substance in America, with increasing rates of use. Some theorists tend to link frequency of use with cannabis dependence. Nevertheless, fewer than half of daily cannabis users meet DSM-IV-TR criteria for cannabis dependence. This study seeks to determine whether the negative aspects associated with cannabis use can be explained by a proxy measure of dependence instead of by frequency of use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
44
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(51 citation statements)
references
References 41 publications
6
44
1
Order By: Relevance
“…In contrast, our results, along with those of Zeisser et al [9] and earlier work by Looby and Earleywine [22], suggest that daily light (i.e. 1 joint) users suffer fewer problems than daily heavy users (2+ joints), such that quantity does matter in relation to the assessment of cannabis-related harms.…”
Section: Unpacking ‘Problematic' Cannabis Usecontrasting
confidence: 57%
See 1 more Smart Citation
“…In contrast, our results, along with those of Zeisser et al [9] and earlier work by Looby and Earleywine [22], suggest that daily light (i.e. 1 joint) users suffer fewer problems than daily heavy users (2+ joints), such that quantity does matter in relation to the assessment of cannabis-related harms.…”
Section: Unpacking ‘Problematic' Cannabis Usecontrasting
confidence: 57%
“…Indeed, patterns of moderate, controlled use predominate for the majority of adult consumers, such that daily cannabis users are often hard to distinguish, in terms of health, social, and economic markers, from individuals who have never used the drug [13,14,15]. Nevertheless, researchers have identified a range of potential harms, particularly in relation to long-term heavy use, while the associated risks of exposure in youth dictate caution and the importance of prevention [16,17,18,19,20,21,22]. …”
Section: Introductionmentioning
confidence: 99%
“…Daily marijuana use is now at its highest rate among college students in more than three decades, and 1 in 10 non-college young adults report daily use (Johnston et al, 2014). Young adults who use marijuana frequently have an increased risk for a variety of short-and long-term consequences, such as injuries and accidents, decreased academic performance, cognitive difficulties such as memory loss, risky sexual behavior, physical complications such as poor lung capacity and difficulty breathing, lower selfconfidence and self-esteem, and psychological difficulties such as increased depression and social anxiety (Buckner et al, 2010;Hall & Degenhardt, 2009;Kalant, 2004;Looby & Earleywine, 2007;Simons et al, 2010;Taylor et al, 2000).…”
Section: Y Oung Adults Are An At-risk Populationmentioning
confidence: 99%
“…Two cross-sectional studies sampling frequent users showed that CUD users had higher rates of internalizing and substance use problems than non-CUD users (Looby & Earleywine 2007; van der Pol et al 2013). Van der Pol et al (2013) compared frequent users to a representative group of Dutch controls and detected higher rates of externalizing disorders, substance use, and childhood adversities (e.g., childhood abuse, parental divorce or absence) in CUD users and non-CUD users compared to non-users.…”
mentioning
confidence: 99%